2022
DOI: 10.7554/elife.81573
|View full text |Cite
|
Sign up to set email alerts
|

Regulated degradation of the inner nuclear membrane protein SUN2 maintains nuclear envelope architecture and function

Abstract: Nuclear architecture and functions depend on dynamic interactions between nuclear components (such as chromatin) and inner nuclear membrane (INM) proteins. Mutations in INM proteins interfering with these interactions result in disease. However, mechanisms controlling the levels and turnover of INM proteins remain unknown. Here, we describe a mechanism of regulated degradation of the INM SUN domain-containing protein 2 (SUN2). We show that Casein Kinase II and the C-terminal domain Nuclear Envelope Phosphatase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 56 publications
(75 reference statements)
0
20
0
Order By: Relevance
“…As homologs of Asi proteins are absent in S. pombe as in other species, INMAD mechanisms may be diverse among organisms. However, increasing evidence has shown that the degradation of INM proteins in plants and mammals also employs the UPS and Cdc48/p97 (Tsai et al, 2016; Huang et al, 2020; Krshnan et al, 2022), raising a general mechanism for INM protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…As homologs of Asi proteins are absent in S. pombe as in other species, INMAD mechanisms may be diverse among organisms. However, increasing evidence has shown that the degradation of INM proteins in plants and mammals also employs the UPS and Cdc48/p97 (Tsai et al, 2016; Huang et al, 2020; Krshnan et al, 2022), raising a general mechanism for INM protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous studies have identified mechanoresponsive post‐transcriptional control over SUN2 levels, suggesting a role for regulated protein degradation pathway. Interestingly, insight into the possible mechanisms at play came from other experimental angles: the study of integral INM protein turnover [41] and crosstalk between lipid composition at the INM and the nuclear envelope proteome [42] (Fig. 3).…”
Section: Regulation Of Sun2 Levels Through Transcriptional Regulation...mentioning
confidence: 99%
“…3). Carvalho and colleagues, focusing on defining mechanisms of protein turnover at the INM, honed in on predicted binding sites for degradation by the Skp1/Cullin/F‐Box family of ubiquitin ligase complexes, specifically containing the F‐Box member βTrCP, in SUN2 [41]. Importantly, SCF βTrCP typically requires phosphorylation of its recognition site in client proteins, opening up an attractive avenue by which signaling pathways could impinge of SUN2 protein levels.…”
Section: Regulation Of Sun2 Levels Through Transcriptional Regulation...mentioning
confidence: 99%
See 1 more Smart Citation
“…We had previously shown that ER expansion interferes with chromosome segregation causing higher rates of micronuclear formation (Merta et al, 2021), suggesting a link between dysregulated lipid synthesis and chromosomal instability in cancer cells. CTDNEP1 influences the lipid profile of the inner nuclear membrane (INM) as well as the stability of the inner nuclear envelope protein Sun2 through direct membrane sensing mechanism (Krshnan et al, 2022; Lee et al, 2023). CTDNEP1 has been implicated in regulating BMP signaling (Satow et al, 2006; Sakaguchi et al, 2013; Hayata et al, 2015; Darrigrand et al, 2020), which also involves nuclear envelope-associated proteins (Bengtsson, 2007).…”
Section: Introductionmentioning
confidence: 99%